Aspects of brutality : anxious concepts in sculpture since 1950 - Lang, Graham Charles (Rhodes University, Faculty of Humanities, Department of Fine Art, 1987)
It would be wrong to suggest that this essay is in any way a comprehensive study of brutal sculpture. Certainly not. There have been many deliberate omissions for reasons which become clear in the text. Very briefly, omissions of certain sculptors and their work are largely due to my wish to avoid repetitive ideas and images. My view in this essay is to provide a cross-section of ideas and works, whereby the reader might gain some insight into the varied nature of this kind of sculpture. Thus, there seemed very little need for endless similarities of concept and expression. It was the diversity which I felt was important. The chapter which discusses concepts of beauty is also not a comprehensive study. This subject demands more than a humble essay to do it any justice. However, my reasons for touching the vague and controversial outline of these concepts were, primarily, to suggest that notions of beauty as the sole criterion in the judgement of art are too limiting, and, consequently, to introduce the concept of vitalism, which I believe is more valid. Finally, I wish to mention the personal motive behind this work. Over the years, I have witnessed the emergence of brutal elements in my own work, which I found disturbing at times. I have never been able to answer satisfactorily the criticism I've received. All I knew was that these things came from a very deep source. It is with this in mind that I embarked on this project, hoping to achieve two things. Firstly, to provide an objective survey of an important development in art, and, secondly , to answer some of my criticism. Foreword, p. 1.
Keywords: Sculpture, Modern -- 20th century; Violence in art